2007
DOI: 10.1097/01.brs.0000261490.90956.2b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Comparison of Posterior Instrumentation Constructs for Spinal Fixation Across the Cervicothoracic Junction

Abstract: The present results demonstrate that the 3.5-mm rod-and-screw construct is the weakest configuration for posterior fixation across the cervicothoracic junction. The dual diameter rod and fixed domino connector constructs were the strongest and demonstrated similar values for yield and ultimate force.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On biomechanical testing, there is no difference between the dual-diameter and solid domino connected rod. 26 In our series, the fixation failure rate was 6% when using a PSS and 15% when using a SHRS. The safety and ease of screw placement with comparable rates of failure make this the preferred method of fixation at the CTJ.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On biomechanical testing, there is no difference between the dual-diameter and solid domino connected rod. 26 In our series, the fixation failure rate was 6% when using a PSS and 15% when using a SHRS. The safety and ease of screw placement with comparable rates of failure make this the preferred method of fixation at the CTJ.…”
Section: Discussionmentioning
confidence: 91%
“…No patient in our series experienced screw or rod breakage, despite biomechanical data suggesting that this construct is inferior across the CTJ compared with dual-rod systems. 26 Thus, in tumor patients undergoing C6-7 decompression, a 3.5-mm screw/rod system provides reliable fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The weakest of construct involved and C6/7, then supplemented with posterior fixation using bilateral lateral mass screws at C5 and C6, and bilateral C7 laminar screws (28 and 32 mm). paired 3.5 mm diameter rods, which was shown to be inferior to paired 3.5 mm/5.5 mm transitional rods, as well as paired 3.5 and 5.5 mm rods joined with solid or hinged domino connectors (33). However, Yang et al showed increased complication rates, blood loss and operating time associated with transitional rods over small rods, with nonetheless similar pseudoarthrosis rates (34).…”
Section: Resultsmentioning
confidence: 99%
“…As a transition zone from the flexible, lordotic cervical spine to the rigid thoracic spine, the cervicothoracic junction is subjected to force concentration. 30 When significant instability exists, most authors have recommended combined anterior-posterior treatment. 4,14,18 This trend is due in part to the limitations of fixation at the cervicothoracic junction.…”
Section: Introductionmentioning
confidence: 99%
“…A biomechanical study of these four constructs (hinged and fixed domino-connectors separate) has been conducted by Tatsumi et al, 30 They concluded that the construct containing all 3.5-mm screws was the weakest and failed consistently at lower loads. The hinged domino construct failed at the hinge axis which was the weakest link in the construct.…”
mentioning
confidence: 99%